Risk factors associated with high altitude sickness among travelers: A case control study in Himalaya district of Nepal. - Sishir Poudel; Laxman Wagle; Mukhiya Ghale; Tara Prasad Aryal; Sushan Pokharel; Binay Adhikari (PLOS Global Public Health)
High elevation adventures are popular among travelers; however, they carry significant health risks, such as altitude sickness. This study aims to identify risk factors associated with high altitude sickness among travelers to Mustang district. A health-facility-based, age-sex matched 1:1 case-control study was conducted in Mustang district hospital, Nepal. Measurements included Acute Mountain Sickness/High Altitude Cerebral Edema/High Altitude Pulmonary Edema assessment via LLS questionnaire, demographics, medical history, ascent rate, and prophylactic medicine intake. Data were collected between September and November, 2023 via predesigned structured questionnaire by trained medical officers in, and analyzed using SPSS version 25. Using binary logistic regression, the study tested potential risk factors associated with altitude sickness. Ethical approval was obtained from the NHRC, and written informed consent was obtained from all participants. A total of 63 cases (individuals with altitude sickness) and 63 controls (without) were interviewed. The mean age of cases and controls was 48.5 years (SD = 16.5) and 48 years (SD = 16.9) respectively. 38 were rapid ascenders, and 88 were slow ascenders. Awareness of altitude sickness was reported by 65 individuals, with 36 taking prophylactic medication (Acetazolamide 125/250mg). Among cases, 8 experienced HACE, 42 had AMS, and 13 had HAPE. Rapid ascent (Adjusted Odds Ratio [AOR]: 6.41, 95% Confidence Interval [CI]: 2.36-17.54), individuals with a previous history of illness (AOR: 10.20, 95% CI: 2.70-38.46), and failing to take prophylactic medication (AOR: 10.01, 95% CI: 1.896-10.680) were linked to an increased risk of altitude sickness. Our study highlights the critical role of ascent speed, previous history of illness, and use of prophylactic measures in development of altitude sickness.